KELAYAKAN MULTIMEDIA INTERAKTIF BERBASIS ADOBE FLASH PADA SUB MATERI GANGGUAN KESEHATAN REPRODUKSI - Azaria, Cut Nabila; Panjaitan, Ruqiah Ganda Putri; ., Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
This research aims to know the feasibility of interactive multimedia using adobe flash based on survey of adolescent reproductive system disorders in Puskesamas Alianyang Pontianak. Method was used  descriptive quantitative research with  technique purposive sampling. Interactive multimedia validated by five media and material experts. Aspect assessed include aspect of software engineering, learning design, and audio-visual communication. The average result of interactive multimedia validation analized found that the aspects of software engineering was 3,70, learning design was 3,62, and audiovisual communication was 3,52. Interactive multimedia using adobe flash was applicable to used as learning media. Keywords: Interactive multimedia, adobe flash, reproductive system disorders